(untitled) (Research, Society and Development, 2020)
The aim of this article is to analyze the satisfaction of health professionals of the Municipal Health Unit of Cotijuba Island - PA. This is a descriptive study with a qualitative approach. The study included 13 health professionals from Cotijuba Island in 2018, whose data were analyzed by Bardin’s content analysis technique. With the results obtained, the axes of analysis adopted, in which they point out the influence of several factors that interfere in the satisfaction of health professionals from classroom, working conditions, motivation, teamwork, management from the perspective of the participants. This study emphasizes the importance of working on the satisfaction of health professionals in the area of Primary Care, as it is essential for the development and success of any institution.